Physico-chemical characteristics of sea urchin shell calcium (Diadema setosum) on Barrang Lompo Island - Hasrianti, Hasrianti; Harianti, Harianti; Awaluddin, Awaluddin; Khairiyah, Zul (Sangia Research Media and Publishing, 2024)
Calcium is a mineral that can be found in the shells of sea urchins. Calcium supplementation in pill form is commonly encountered within the community, derived from both animal and vegetable sources. The objective of this study is to investigate the physico-chemical properties of calcium derived from the shells of the sea urchin species Diadema setosum. The research was conducted between April 2023 and June 2023, involving sample collection on BarrangLompo Island and subsequent testing at the Chemical Laboratory of Pangkep State Agricultural Polytechnic. The study methodology employed entailed conducting experiments within a controlled laboratory setting where distinct treatment media were utilized. Specifically, the treatments employed were denoted as Treatment A, characterized by a temperature of 1000 °C, and Treatment B, characterized by a temperature of 500 °C.The findings of the study conducted on calcium derived from sea urchin shells (Diadema setosum) revealed that the calcium exhibited two distinct colors, namely dark brown and light brown. Additionally, some samples possessed an odor, while others were odorless. Furthermore, the texture of the calcium was observed to be smooth. The average yield values for treatment A and treatment B were determined to be 1.49 and 1.80, respectively. Moreover, the average water content values for treatment A and treatment B were found to be 1.29 and 1.06, respectively. Lastly, the average calcium content values for treatment A and treatment B were measured to be 83.30 and 78.20, respectively. Based on the results of statistical analysis, it is evident that there is no statistically significant disparity observed in the yield, water content, or calcium content of sea urchin shell calcium flour (Diadema setosum).